Fractal analysis of major faults and fractal dimension of lineaments in the Indo-Gangetic Plain on a regional scaleKey points - Vipin Chauhan; Jagabandhu Dixit (Earthquake Science, 2024)
The Indo-Gangetic Plain (IGP) is one of the most seismically vulnerable areas due to its proximity to the Himalayas. Geographic information system (GIS)-based seismic characterization of the IGP was performed based on the degree of deformation and fractal dimension. The zone between the Main Boundary Thrust (MBT) and the Main Central Thrust (MCT) in the Himalayan Mountain Range (HMR) experienced large variations in earthquake magnitude, which were identified by Number-Size (NS) fractal modeling. The central IGP zone experienced only moderate to low mainshock levels. Fractal analysis of earthquake epicenters reveals a large scattering of earthquake epicenters in the HMR and central IGP zones. Similarly, the fault fractal analysis identifies the HMR, central IGP, and south-western IGP zones as having more faults. Overall, the seismicity of the study region is strong in the central IGP, south-western IGP, and HMR zones, moderate in the western and southern IGP, and low in the northern, eastern, and south-eastern IGP zones.